Construyendo el espacio público (2017)
This thesis Project was focused on developing one of the new stations for the new public transportation system in Bogotá, Colombia. The fundamental base of this intervention consisted on taking maximum advantage of existing public space and the suitable implantation of this urban equipment in order to secure the use of this new transportation system to the neighborhood and citys' habitants.